Influence of the excavator hydraulic system efficiency on the productivity - Michal Jůza; Petr Heřmánek (Research in Agricultural Engineering, 2023)
This paper presents the experimental research of factors influencing the UDS 214 excavator efficiency. The hydraulic oil flow rate is measured in hydraulic circuits for controlling the moving of the bucket of the UDS 214 excavator. From the measured values, the total power losses of the individual hydraulic circuits and their efficiencies are evaluated by calculations and measurements. Furthermore, the times of the excavator cycles during a soil excavation and loading of the transport vehicle were measured. From the measured operating cycle times of the excavator, the average value of the operating cycle time was evaluated and, from this average time, the theoretical performance and the operating performance of the given excavator in the given operational states were calculated. Then, at the end of the paper, the individual calculated power losses as well as the efficiencies of the hydraulic circuits for controlling the moves of the excavator are evaluated. According to the findings, the swing hydraulic circuit of the excavator, which has the second highest power loss of 5.926 kW and its percentage in the average tested cycle time of the excavator is 48%, seems to be a suitable hydraulic circuit for the innovation.